Elaboración del Plan Barrial de Emergencias para los Barrios Panamá y Caraguaja de Campoalegre (Huila). (2021)
The present investigation refers to the elaboration of the neighborhood plan for the preparation, prevention and response to emergencies in the Panama and Caraguaja neighborhoods of the municipality of Campoalegre -Huila; This plan can be defined as one that allows the identification of the threats, vulnerability and risk to which a community is subjected. Understanding as a threat the probability of occurrence of a natural or man-induced phenomenon that can cause serious damage to a locality or territory, these threats according to their origin can be classified as natural that originate in the dynamics of the earth, These events can be related to water, climate, as is the case of heavy rains, rising rivers, frosts or droughts. In socio-natural threats whose occurrence and intensity of their effects involve human beings, examples of this type of threat are floods, droughts or landslides that are often more frequent and intense due to deforestation and inadequate management. of the soils, human threats directly attributable to the action of the human being on elements of nature, examples of this are the contamination of water, land and air.